Optimising Religious Education in Poland in the Age of Secularisation - Mąkosa, Paweł (Verbum Vitae, 2024)
The dynamic secularisation of Polish young people and the fact that many of them are opting out of religious classes prompts a critical analysis of the current model of Religious Education and the development of proposals that respond to contemporary socio-cultural challenges. In others words this article will seek to outline potential directions for modifying the current Religious Education model intended for secondary school students in Poland. This paper attempts to provide a synthetic answer to the following questions: Why is Religious Education in secondary schools today not leading to the expected results? What elements of it are inadequate for contemporary conditions? What should the model of Religious Education for young people look like in the context of a decline in religiousness? Where and how should catechesis be provided? This paper contributes to the discussion on the shape of Religious Education for young people in a changing society.